Transesterification via different intensification methods using waste feedstocks and waste heterogeneous catalysts - Intan Shafinaz, Abd Manaf (2020)
Feedstock cost is one of the main attentions in biodiesel production and researchers intensively seeking for a low-cost feedstock in order to make the process viable. Heterogenous catalyst helps offer less water generation, ease the catalyst separation and able to reused. In this present work, the transesterification of Aglaia korthalsii seed oil and catfish fat using barnacle and potassium loaded on tilapia fish bone as heterogeneous catalysts were attempted. It has been found that 900 °C at 2 h calcination is the optimum condition for barnacles and tilapia fish bone to transform the CaCO3 into CaO. While, 10% potassium had successfully loaded on tilapia fish bone using wet impregnated treatment. The catalyst had been characterized using Thermogravimetric/differential Thermal analysis (TGA/DTA), X-Ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Brunauer, Emmett and Teller surface area (BET), X-Ray Fluorescence (XRF), Field Emission Scanning Electron Microscopy (FESEM), Energy-dispersive X-Ray Spectroscopy (EDX) and basic strength using Hammett indicators. ANOVA results revealed that the experimental model is well significant and under the suggested optimal reaction conditions of 12.2:1 MeOH:oil molar ratio and 4.7 wt.% catalyst (3 h reaction duration at 65 °C), Aglaia korthalsii seed oil was successfully converted into methyl ester with highest conversion of 97.12 ± 0.49 wt.%. Whereas the catfish fat shows the conversions at 93.7 wt.% for 3 h reaction duration at 65 °C, MeOH: oil molar ratio at 12:1 and 5 wt.% catalyst as an optimal reaction condition. Both catalysts can be reused up to four times maintaining methyl ester content of 65% and 70%, respectively. The catalyst could tolerate up to maximum level of 4% free fatty acid and 3% moisture with the methyl ester conversion above 94 wt.%. Among all methods, homogenizer show the best activation energy below 30 kJ/mol. The methyl esters produced were found to conform the key specifications for biodiesel follow the EN 14103 standard. The engine performance of blended 5 % biodiesel was investigated on a single cylinder 4-stroke diesel engine. The results indicated that the blended 5 % biodiesel gave maximum fuel consumption up to 1.7 kg/h whereas the neat biodiesel was at 1.45 kg/h. It has been proven that biodiesel will help in reducing the heating value and lower the energy input.